2018
DOI: 10.1038/s41598-018-22208-w
|View full text |Cite
|
Sign up to set email alerts
|

SESN2 negatively regulates cell proliferation and casein synthesis by inhibition the amino acid-mediated mTORC1 pathway in cow mammary epithelial cells

Abstract: Amino acids (AA) are one of the key nutrients that regulate cell proliferation and casein synthesis in cow mammary epithelial cells (CMEC), but the mechanism of this regulation is not yet clear. In this study, the effect of SESN2 on AA-mediated cell proliferation and casein synthesis in CMEC was assessed. After 12 h of AA starvation, CMECs were cultured in the absence of all AA (AA−), in the presences of only essential AA (EAA+), or of all AA (AA+). Cell proliferation, casein expression, and activation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
49
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 56 publications
9
49
1
Order By: Relevance
“…In the current study, the stimulating effects of EAA and SARS led to enhanced cell viability or cell proliferation (MKI67)/cell cycle progression (CCND1) and lower cell cycle arrest (SFN) in BMEC. The overall results confirm earlier findings that EAA sufficiency (Luo et al, 2018) and LARS (Wang et al, 2014) promote cell viability, cell cycle, and β-casein production in BMEC. In summary, SARS may help EAA accelerate cell cycle progression of BMEC, which could further promote mammary cell population expansion and increase milk production.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In the current study, the stimulating effects of EAA and SARS led to enhanced cell viability or cell proliferation (MKI67)/cell cycle progression (CCND1) and lower cell cycle arrest (SFN) in BMEC. The overall results confirm earlier findings that EAA sufficiency (Luo et al, 2018) and LARS (Wang et al, 2014) promote cell viability, cell cycle, and β-casein production in BMEC. In summary, SARS may help EAA accelerate cell cycle progression of BMEC, which could further promote mammary cell population expansion and increase milk production.…”
Section: Discussionsupporting
confidence: 91%
“…The markedly enhanced (decreased) expression of SARS and β-casein and the increase (decrease) of EAA re-stimulation (re-deprivation) time suggest that EAA affected the protein abundance of SARS and β-casein in similar patterns and that these effects were timedependent. As Luo et al (2018) reported, when BMEC were first treated with AA deprivation and then resupplied with AA or EAA for the same durations as in this study, the protein abundance of mTOR at the lysosomal outer surface of BMEC (indication of mTOR activation) was gradually enhanced along with the increase of AA or EAA treatment time, which reached the maximum at 6 h of AA/EAA treatment. Therefore, the activation of the mTOR system may be altered along with different treatment time of EAA deficiency and EAA sufficiency.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations